LOCAL ADAPTATION AS THE FOUNDATION OF UKRAINE’S FOOD SYSTEM RESILIENCE UNDER WAR CONDITIONS - Рибак, Я. Я. (ПРОДОВОЛЬЧІ РЕСУРСИ, 2025)
Subject. This study investigates the resilience of Ukraine’s agro-food system during the full-scale war, focusing on the disruptive impact of military aggression and the adaptive responses it triggered. Special attention is given to the transformation of local food systems, the restoration of supply chains, and the revitalization of cooperative mechanisms under conditions of institutional fragmentation and crisis. Purpose. The primary aim is to examine the potential of local cooperation, institutional adaptation, and innovation as key pillars for strengthening food security in Ukraine under wartime conditions. The research seeks to identify structural barriers and propose policy-oriented solutions that support autonomous, community-based food initiatives. Methods. The research is grounded in a multi-method approach combining comparative historical analysis of cooperative movements (notably in Western Ukraine during the 1920s–1930s), statistical review of food system disruptions, and institutional diagnostics. Key factors analyzed include legal fragmentation, low trust in institutions, financial instability, and the limited availability of managerial capacity. Results. The study reveals that despite the war-induced collapse of centralized supply systems, local communities have demonstrated a capacity for self-organization, restoring food accessibility and economic functions through ad hoc partnerships. Wartime realities have fostered innovation in food logistics, including digital cooperation tools, short supply chains, and hybrid civil-public alliances. Historical precedents of Ukrainian cooperation movements provide both cultural legitimacy and operational blueprints for contemporary applications. Comparative insights from Central and Eastern Europe underscore the value of embedding such initiatives into a supportive regulatory framework. Scope of results. The results can inform national and local strategies for post-war food system recovery, contributing to sustainable food self-sufficiency, institutional resilience, and inclusive economic rebuilding. The proposed policy of “facilitated cooperative entry” can foster long-term stabilization and technological renewal in the agro-food sector.